Limit on B0s oscillation using a jet charge method - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1995)
A lower limit is set on the Bs0 meson oscillation parameter Δms using data collected from 1991 to 1994 by the ALEPH detector. Events with a high transverse momentum lepton and a reconstructed secondary vertex are used. The high transverse momentum leptons are produced mainly by b hadron decays, and the sign of the lepton indicates the particle/antiparticle final state in decays of neutral B mesons. The initial state is determined by a jet charge technique using both sides of the event. A maximum likelihood method is used to set a lower limit of Δms. The 95% confidence level lower limit on Δms ranges between 5.2 and ̷6.5(h̷c2) ps−1 when the fraction of b quarks from Z0 decays that form Bs0 messons is varied from 8% to 16%. Assuming that the B0s fraction is 12%, the lower limit would be ̷Δms> 6.1(h̷c2) ps−1 at 95% confidence level. For xs = ΔmsτBs, this limit also gives xs > 8.8 using the B0s lifetime of τBs = 1.55 ± 0.11 ps and shifting the central value of τBs down by 1σ.